Maximal terahertz emission in high harmonic generation from 3D Dirac semimetals - Lim, Jeremy (2022)
Unlike conventional semiconductor platforms, 3D Dirac semimetals (DSMs) require relatively low input laser intensities for efficient terahertz (THz) high harmonic generation (HHG), making them promising materials for developing compact THz light sources. Here, we show that 3D DSMs’ high nonlinearity opens up a regime of nonlinear optics where extreme subwavelength current density features develop within nanoscale propagation distances of the driving field. Our results reveal orders-of-magnitude enhancement in HHG intensity with thicker 3D DSM films, and show that these subwavelength features fundamentally limit HHG enhancement beyond an optimal film thickness. This decrease in HHG intensity beyond the optimal thickness constitutes an effective propagation-induced dephasing. Our findings highlight the importance of propagation dynamics in nanofilms of extreme optical nonlinearity.